Instability and sensitivity to imperfection of conical shell subjected to axial compression - Mahidan, Fairuz Mardhiah (2021)
Shell structures have been widely used in engineering applications such as pipelines, aerospace, marine structures, and cooling towers. Occurring suddenly and generally inadvertent due to its nature, buckling is one of the main failure considerations in the design of these structures. The presence of defects, such as geometric imperfection, uneven loading, the boundary condition of the shell, material discontinuity/crack imperfection, and so on in shell structures may severely compromise their buckling behavior and jeopardize the structural integrity. In this study, experimental and numerical investigations on the buckling behavior of axially compressed conical shell with uneven axial length imperfection were carried out. The effect of imperfection amplitude, wave number, and wave type were investigated. Initial geometric imperfection in the form of (i) sinusoid waves, (ii) triangle waves, and (iii) square waves having different wave number are explored. This thesis contains experimental data verification and further Finite Element (FE) prediction. Excellent repeatability between experimental results with only 0% to 7% of error was revealed. Abaqus FE was used to simulate the numerical modelling. The imperfection amplitude and shape highly influenced the load-carrying capacity of conical shells. Triangular waves yields the lowest imperfection sensitivity in comparison to other wave shape. Furthermore, the influence of wave number was also studied for each wave shapes. It was found that the wave number has insignificant influence on the buckling load of the axially compressed cones. In the next step, a comparison between different imperfection approach, namely (i) Eigenmode imperfection, (ii) Single and Multiple Load Indentation (SLI and MLI), (iii) crack imperfection, and (iv) uneven axial length imperfection was carried out to determine the worst knockdown factor (KDF) for axially compressed steel conical shell. As predicted, imperfection severely affected the buckling strength of conical shells, and the decrease in buckling strength is heavily reliant on the imperfection approach. It is apparent that for axially compressed cones with radius-to-thickness ratio, r1/t = 25, uneven axial length imperfection was seen to produce the lowest buckling load, followed by eigenmode imperfection, crack imperfection, and load indentation for imperfection amplitude 0 < A < 1.68. Increasing the imperfection amplitude, A, beyond this level (A ≥ 1.68), the highest reduction in buckling load was found to be eigenmode imperfection, followed by uneven axial length, crack and load indentation. Furthermore, based on ECCS 2008 recommendation for imperfection tolerance, the lower bound curve which can be used for design recommendation purposes has been proposed for the worst imperfection approach case (uneven axial length and eigenmode imperfection) for different conical shell geometry configurations. Finally, the proposed lower bound curve was compared with the plot of NASA SP-8019 recommended imperfection correlation factor for axially compressed cone. Results showed that the proposed lower bound curve for axially compressed conical shells with uneven axial length imperfection is notably higher than the NASA SP-8019 KDF by 7%. However, axially compressed conical shells with eigenmode imperfection were seen to underestimate NASA’s KDF by 55%, particularly for elastic buckling.